Distinct Bacterial Communities Associated with the Coral Model Aiptasia in Aposymbiotic and Symbiotic States with Symbiodinium - Röthig, Till; Costa, Rúben M.; Simona, Fabia; Baumgarten, Sebastian; Torres, Ana F.; Radhakrishnan, Anand; Aranda, Manuel; Voolstra, Christian R. (Frontiers in Marine Science, 2016)
Coral reefs are in decline. The basic functional unit of coral reefs is the coral metaorganism or holobiont consisting of the cnidarian host animal, symbiotic algae of the genus Symbiodinium, and a specific consortium of bacteria (among others), but research is slow due to the difficulty of working with corals. Aiptasia has proven a tractable model system to elucidate the intricacies of cnidarian-dinoflagellate symbioses, but characterization of the associated bacterial microbiome and the underlying genomic features relevant for bacterial selection and control is required to provide a complete and integrated understanding of holobiont function. In this work, we characterize and analyze the microbiome of aposymbiotic and symbiotic Aiptasia and show that bacterial associates are distinct in both conditions. We further show that key microbial associates can be cultured without their cnidarian host. Our results suggest that bacteria play an important role in the symbiosis of Aiptasia with Symbiodinium, a finding that underlines the power of the Aiptasia model system where cnidarian hosts can be analyzed in aposymbiotic and symbiotic states. The characterization of the native microbiome and the ability to retrieve culturable isolates contributes to the resources available for the Aiptasia model system. This provides an opportunity to comparatively analyze cnidarian metaorganisms as collective functional holobionts and as separated member species. We hope that this will accelerate research into understanding the intricacies of coral biology, which is urgently needed to develop strategies to mitigate the effects of environmental change.